PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN IPAS MATERI HARMONI DALAM EKOSISTEM KELAS V SEKOLAH DASAR - Oktariani, Imelda; Marhamah, Marhamah; Kuswidyanarko, Arief (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to produce Canva-based interactive media products for students in class V of SD Negeri 229 Palembang as a learning resource in the learning process. This research is a type of research and development using the ADDIE model, namely analysis, design, development, implementation, evaluation. Data collection techniques in this research were observation and questionnaire sheets. The data analysis techniques in this research are validation data analysis and analysis of student responses. Based on the results of data analysis managed, this research produces interactive media material on harmony in an ecosystem that is valid and practical. The validity aspect was obtained through a validation sheet by 2 validators and 1 teacher, getting an average score of 92%. The practicality aspect was obtained based on the average student response questionnaire of 87.99%, so it can be said to be very practical. So it can be concluded that the interactive multimedia learning media that has been developed is valid and very practical.